2004
DOI: 10.4049/jimmunol.173.3.1738
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of the CD8-Dependent Initial Reduction in Tumor Volume Is Not Limited by Contact-Dependent Perforin, Fas Ligand, or TNF-Mediated Cytolysis

Abstract: Established EG7 tumors expressing OVA and growing at an intradermal site become rapidly reduced in size following adoptive therapy with in vitro-generated type I CD8 T cell (Tc1) effectors generated from naive CD8 T cells from transgenic TCR OVA-specific mice. Tc1 effectors kill EG7 target cells in vitro by a perforin-dependent mechanism. However, we show that there is no quantitative diminution of the initial phase of antitumor activity in vivo, whether the Tc1 effectors are derived from perforin-, Fas ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
5
37
0
Order By: Relevance
“…This result would correlate with previous data on CD8 cells obtained from Bcl-x L transgenic mice in which Bcl-x L antagonized apoptosis of effector cells, but only delayed the contraction phase of an Ag-induced CD8 T cell response rather than preventing it (32). Recent results have suggested that recruitment of host cells is essential to the therapeutic action of adoptively transferred CD8 cells, rather than these cells directly targeting the tumor (27,33). If so, long-term protection will then be mediated by host cells and will not require adoptive CD8 cells.…”
Section: Discussionsupporting
confidence: 80%
“…This result would correlate with previous data on CD8 cells obtained from Bcl-x L transgenic mice in which Bcl-x L antagonized apoptosis of effector cells, but only delayed the contraction phase of an Ag-induced CD8 T cell response rather than preventing it (32). Recent results have suggested that recruitment of host cells is essential to the therapeutic action of adoptively transferred CD8 cells, rather than these cells directly targeting the tumor (27,33). If so, long-term protection will then be mediated by host cells and will not require adoptive CD8 cells.…”
Section: Discussionsupporting
confidence: 80%
“…Perforin-deficient mice were reported to be more susceptible to tumor development in some models [5][6][7][8], while other studies found that perforin-deficient CTL were fully capable of exerting anti-tumor activity in vivo [9][10][11][12][13]. Similarly, CD95L-dependent effector mechanisms have been shown to be important in some models [14][15][16] but not in others [9,13,17]. The release of soluble factors represents an additional mechanism by which CD8 T cells could exert anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…An early study in mice revealed that rejection of pulmonary metastases by cultured tumorspecific CD8 T cells correlates better with their capacity to produce IFN-c than with their cytotoxicity in vitro [18]. More recent studies using IFN-c-deficient mice have provided compelling evidence for the important role of IFN-c in T cell-mediated tumor cell rejection [7,9,10,13,14,[19][20][21][22][23][24][25][26]. Various possibilities can be envisaged to explain the anti-tumor activity of IFN-c: first, IFN-c is known to increase MHC expression and antigen presentation, thereby rendering tumor target cells more susceptible to CTL attack [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…IFN-␥ can activate macrophages, enhance Ag processing, and increase MHC expression, including up-regulation of class I expression on tumor cells, making them more susceptible to CTL lysis. IFN-␥ produced by CD8 T cells responding to tumor Ag has been shown to be critical for E.G7 tumor rejection in an adoptive immunotherapy model (30). To determine whether the OT-I cells that were responding to tumor-derived Ag were capable of producing IFN-␥, cells isolated from the tumor and DLN were restimulated with OVA-peptide Ag in vitro and then stained with Abs to IFN-␥.…”
Section: Responding Cd8 T Cells Have An Effector Phenotypementioning
confidence: 99%